Exploring Students’ Mathematical Reasoning Behavior in Junior High Schools: A Grounded Theory - Rohati Rohati; Yaya S. Kusumah; Kusnandi Kusnandi (Education Sciences, 2023)
Mathematical reasoning is an essential ability that students must have in every mathematics lesson. However, student behavior during the process of mathematical reasoning has yet to be widely studied. This research explores the mathematical reasoning behavior of selected eighth-grade students to solve problems requiring a mathematical reasoning process. A qualitative methodology based on grounded theory was implemented, which included an in-depth analysis of student answers and student interviews. The data show that students are engaged in imitative, algorithmic, semi-creative, and creative reasoning behavior. Next, an in-depth explanation was carried out for four students from each level of mathematical reasoning behavior. Students from the imitative, algorithmic, semi-creative, and creative reasoning behavior groups showed consistency in answers and behavior for the given problems. The findings of this study can encourage teachers to focus on fostering the highest level of mathematical reasoning, namely creative mathematical reasoning, in students.